Short-term outcomes in early term infants (born at 37 or 38 weeks): a retrospective investigation - Kitamura, Tsubasa; Tabata, Kyosuke; Murano, Yayoi; Yoneoka, Daisuke; Nakazawa, Tomoyuki; Sakamaki, Ken; Shoji, Hiromichi (Frontiers in Pediatrics, 2024)
The present study was aimed to understand short-term outcome in early term infants. Early term infant is a concept established recent decades and their outcomes are not well-known. This single center study with 4669 infants assessed short-term outcomes. Compared to infants born later than 39 weeks of gestation, early term infants had higher odds ratio for hospitalization, hypoglycemia, and apnea. The analysis performed 37 and 38 weeks of gestation separately revealed higher odds ratio of hospitalization, feeding disorder, hypoglycemia, apnea in 37 weeks of gestation. Taking increasing number of early term infants, health care practitioners should know these outcomes, as they are managed as normal term infants. Moreover, when planning electric cesarian section, as outcomes of 38 weeks is better than 37 weeks of gestation, our study suggest choosing cesarian section at 38 weeks of gestation.